2018
DOI: 10.1080/15384047.2018.1491502
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment using apatinib in intractable brain edema: A case report and literatures review

Abstract: The treatment of intractable vasogenic brain edema (VBE) caused by tumor and irradiation is challenging. Traditional intervention strategy includes dehydration and glucocorticoids accompanied by obvious side effects and minor effects after long-term use. Novel treatment needs to be found urgently. Recently, vascular endothelial growth factor (VEGF)/VEGFR pathway has been revealed to be essential in VBE. Therefore, tyrosine kinase inhibitor (TKI) targeting VEGFR which blocks (VEGF)/VEGFR signal might be effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Apatinib is another oral TKI that selectively targets VEGFR-2 to inhibit tumor angiogenesis ( 14 ), and apatinib has reported activity in BC ( 15 , 16 ). However, BC with chest wall metastasis (CWM) has a rich blood supply because of the high expression of angiogenic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Apatinib is another oral TKI that selectively targets VEGFR-2 to inhibit tumor angiogenesis ( 14 ), and apatinib has reported activity in BC ( 15 , 16 ). However, BC with chest wall metastasis (CWM) has a rich blood supply because of the high expression of angiogenic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al [ 4 ] reported that apatinib could shrink refractory radiation-induced brain edema in patients with NSCLC and NHL, and dramatically improve their symptoms. Song et al [ 5 ] found that apatinib can shrink PTBE in a remarkably short period of time. Li et al [ 17 ] reported that low-dose apatinib monotherapy showed excellent efficacy in the treatment of symptomatic BMs in 1 patient with triple-negative breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] Some case reports have focused on the effects of treatment with apatinib for BM and peritumoral brain edema (PTBE) or radiation-induced brain edema. [ 4 , 5 ] Gene mutation-targeting drugs have a good effect on BM in NSCLC with corresponding gene mutation, however, there are no particularly effective drugs for BM in primary lung MEC. In our present case, we report for the first time that FSRT and apatinib were used in combination to treat a patient with primary lung MEC who had limited BM with PTBE.…”
Section: Introductionmentioning
confidence: 99%
“…• anti-VEGFR-1 antibody inhibits ECM invasion • PAMs-TLR-2 interaction promotes pro-inflammatory astrocytic activation Esen et al, 2004 • TLR2 promotes pro-inflammatory microglial activation Kielian et al, 2005a • TLR2 regulates pro-inflammatory mediators' expression Kielian et al, 2005b • MyD88 promotes a protective inflammatory response in mouse brain abscess mode and subsequent opening of the BBB (Davies, 2002). Moreover, VEGF may induce fenestration in the endothelium and thus increase capillary permeability partially by inhibiting the TJ proteins claudin-1 and claudin-5 (Roberts and Palade, 1995;Song et al, 2018). Along with metastatic cells, tumor-infiltrating lymphocytes in the peritumoral edema also contribute to VEGF expression.…”
Section: Brain Metastasismentioning
confidence: 99%